Leaf decomposition and ecosystem metabolism as functional indicators of land use impacts on tropical streams - Silva-Junior, Eduardo F.; Moulton, Timothy P.; Boëchat, Iola G.; Gücker, Björn (Ecological indicators, 2014)
•We tested the suitability of ecosystem processes as indicators of land use impacts.•Stream respiration was related to N concentration and to an urban land cover gradient.•Even in little urbanized catchments, impacts were considerable.•Primary production was related to agricultural land cover, but not to nutrients.•Fast leaf decomposition was an indicator of pristine conditions in the studied streams. Organic matter decomposition and ecosystem metabolism have been suggested as promising functional indicators of stream ecosystem integrity, but tests of their applicability to tropical systems are rare. Here, we tested the suitability of the ecosystem processes leaf decomposition (LD), community respiration (CR) and gross primary production (GPP) as functional indicators of catchment and riparian corridor land use impacts on 16 rural, tropical headwater streams. Agricultural and urban land cover contributed 0.0–78.3% and 0.0–8.3%, respectively, to total catchment land cover, and 0.0–61.2% and 0.0–7.8%, respectively, to land cover in a riparian corridor of 20m width of the investigated streams. Median rates of GPP and CR in the studied streams were 0.4gO2m−2d−1 (0.0–1.6, min–max) and 3.3gO2m−2d−1 (1.8–15), respectively. According to the double exponential model, median leaf litter decay coefficients of the recalcitrant and the labile litter fraction were 0.006d−1 (−0.017 to 0.016) and 0.15d−1 (0.06–0.86), respectively. While land use in the riparian corridor was correlated to the studied ecosystem processes, whole catchment land use did not exhibit such relations. Nitrogen enrichment and increased CR, both related to urban land use, were the main impacts, indicating that already low levels of urban land cover can have considerable effects on stream integrity in the investigated rural tropical landscape. Although spanning a much wider gradient, agricultural land cover was a less important stressor, and stimulated GPP was related to stream morphology, but not to nutrient enrichment. Leaf decomposition was negatively correlated with both the agricultural and the urban impacts, suggesting that high rates of leaf decomposition are an indicator of pristine conditions in the studied streams. In conclusion, measurements of LD, CR and GPP appear to be suitable, and complementary functional indicators of stream integrity and provided insights into mechanisms of land use impacts on streams in tropical rural catchments.